2017
DOI: 10.1080/00071668.2017.1332404
|View full text |Cite
|
Sign up to set email alerts
|

Performance and digestive function of broiler chickens given grit in the diet

Abstract: 1. A series of experiments were carried out to study the effect of grit on broiler performance, gizzard development and fate of grit in the digestive tract. 2. In Experiment 1, performance, gizzard weight and content of grit in the gizzard of broiler chickens given access to granite-type grit was investigated. In Experiment 2, the effect of grit stones on performance and gizzard development was assessed in diets with or without whole wheat. 3. In Experiment 3, the effect of grit in the form of zeolite, granite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Some researchers [1,2,11] stated that there were no differences with using grit among the groups in terms of carcass yield and relative percentages of organ weight. Some early studies [1,[26][27][28] showed that granite grit usage increased the weight of gizzard but had no effect on performance of broilers, which is also consistent with our results. This result can be explained by a large proportion and different size of the grit stones consumed by chicks retained in the gizzard [2,29] .…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers [1,2,11] stated that there were no differences with using grit among the groups in terms of carcass yield and relative percentages of organ weight. Some early studies [1,[26][27][28] showed that granite grit usage increased the weight of gizzard but had no effect on performance of broilers, which is also consistent with our results. This result can be explained by a large proportion and different size of the grit stones consumed by chicks retained in the gizzard [2,29] .…”
Section: Discussionsupporting
confidence: 93%
“…Although the size of BIPS particles used in this study was 1.5 mm, which is representative of ground grain particles and within the maximum size of particles to pass through gizzard (0.5–1.5 mm), consistency could be one of the factor for the slow passage rate of the BIPS as particle hardness will influence the passage rate (Ferrando et al, ). A previous study in chickens showed that grit stones may occasionally be retained in the gizzard and pass through the small intestine without being grounded (Svihus et al, ). Moreover, when comparing the BIPS and TiO 2 methods, a significant disagreement on the passage rate of these markers could be detected (Figure ).…”
Section: Discussionmentioning
confidence: 99%